2011
DOI: 10.4049/jimmunol.1001877
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and Sustained CD8+ T Cell Responses with an Adenoviral Vector-Based Hepatitis C Virus Vaccine Encoding NS3 Linked to the MHC Class II Chaperone Protein Invariant Chain

Abstract: Potent and broad cellular immune responses against the nonstructural (NS) proteins of hepatitis C virus (HCV) are associated with spontaneous viral clearance. In this study, we have improved the immunogenicity of an adenovirus (Ad)-based HCV vaccine by fusing NS3 from HCV (Strain J4; Genotype 1b) to the MHC class II chaperone protein invariant chain (Ii). We found that, after a single vaccination of C57BL/6 or BALB/c mice with Ad-IiNS3, the HCV NS3-specific CD8+ T cell responses were significantly enhanced, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 50 publications
1
56
0
Order By: Relevance
“…These constructs have a previously documented in vivo protective capacity against viral infection, regardless of whether perforin or IFN-g represents the major antiviral effector mechanism (20,21). Through challenge of vaccinated mice with a recombinant strain of L. monocytogenes modified to secrete part of LCMV GP (Lm-GP33), we obtained basic proof-of-concept for the hypothesis that the adenovirus-based vaccine strategy will confer protection against an intracellular bacterial infection like L. monocytogenes and that protection might be improved by tethering of the target Ag to Ii.…”
mentioning
confidence: 99%
“…These constructs have a previously documented in vivo protective capacity against viral infection, regardless of whether perforin or IFN-g represents the major antiviral effector mechanism (20,21). Through challenge of vaccinated mice with a recombinant strain of L. monocytogenes modified to secrete part of LCMV GP (Lm-GP33), we obtained basic proof-of-concept for the hypothesis that the adenovirus-based vaccine strategy will confer protection against an intracellular bacterial infection like L. monocytogenes and that protection might be improved by tethering of the target Ag to Ii.…”
mentioning
confidence: 99%
“…Surprisingly, this strategy improved not only CD4+ T cell responses, but also the kinetics, breadth, magnitude and stability of the CD8+ T cell response via increased MHC class I presentation and independently of MHC class II . We have since then confirmed these findings with a variety of antigens and are able to conclude that the level of antigen presentation on the adenovirus transduced cell is a limiting factor with regard to the speed and breadth of CD8+ T cell responses (Hoegh-Petersen et al, 2009;Mikkelsen et al, 2011;Sorensen et al, 2009). Given the apparent dichotomy of fast hematopoietic and chronic nonhematopoietic antigen presentation in adenoviral vaccination, this is highly consistent with the hypothesis that the above described strategies work at least in part to increase the first wave of antigen presentation mediated by dendritic cells directly transduced by the vector (see figure 2).…”
Section: Increasing the Breadth Of The Cd8+ T Cell Responsementioning
confidence: 57%
“…Absence of a dominant epitope in an Ii-linked construct may dramatically increase subdominant responses Linking the vaccine Ag expressed from an adenoviral vector to the MHC class II-associated Ii has proved successful in eliciting increased numbers of Ag-specific CD8 + T cells in several studies (29,30,(35)(36)(37). However, the effect of Ii linkage varies with the selected Ag, and we have previously observed that the NP of LCMV does not seem to benefit from Ii linkage in terms of numbers of NP396 (dominant epitope)-specific CD8 + T cells and protection from LCMV infection (24) (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bishop (Oxford University, Oxford, U.K.) via Annette Oxenius (Swiss Federal Institute of Technology, Zurich, Switzerland) and grown on CV-1 cells at low multiplicity of infection; quantification was performed as described previously (30). Mice were infected i.p.…”
Section: Virusesmentioning
confidence: 99%
See 1 more Smart Citation